Clay, hand building - Sapiro, Maurice (Worcester, Mass. : Davis Publications, 1979)
Examines a variety of hand-forming techniques for working with clay, including pinch, coil, and slab construction, and features a photographic gallery of finished projects.
Adult
Keywords: Pottery craft; Pottery craft